The collaboration of digital platforms in the application and collection of taxes - Ruíz Hidalgo, Carmen (2021)
The use of digital platforms for the provision of services and sale of goods has increased in recent years, thereby transforming the performance of markets. These transactions have called into question some of the pillars on which taxation has been based, due to the tax obligations generated. At the same time, new opportunities are created to help both tax administrations and taxpayers in the application of the tax system, also facilitating its subsequent control.Since digital platforms are destined to become important collaborating agents of the tax administration, throughout this article, the authors identify the way in which they affect the application and collection of taxes. First, they address the issue of tax enforcement, reviewing the tasks and obligations of these platforms in this regard. Then, they cover the issue of tax collection and the way in which the platforms collaborate with it.